Analisa Perbandingan Pengaruh Variasi Material Rotor dan Stator Terhadap Nilai Efisiensi dan Losses Pada Permanent Magnet Sychronous Generator (PMSG) Menggunakan Finite Elemen Method (FEM) - Adam Mandala (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2022)
The need for electrical energy continues to increase and the condition of natural resources is getting depleted, making researchers to be able to produce renewable energy that can be obtained from the surrounding environment. One of the energies that can be developed is wind energy, wind energy can be used as a wind power plant (PLTB). The generator used in this topic is a 12-slot 8-pole permanent magnet synchronous generator (PMSG), the generator is a generator that can produce micro-scale electrical energy. The purpose of this study is to compare the efficiency and losses in the material contained in the generator rotor and stator, namely M 15A, Arnon, and No. 12 materials with additional variations in RPM and load on the generator, using the Finite Element Method (FEM) Software, namely modeling and analysis of electromagnetic components using MagNet Infolytica 7.5 software, the data obtained from the software will be the source of data to be analyzed, so that the comparison of the efficiency of the permanent magnet synchronous generator (PMSG) material can be known. Loading simulation is used to find the value of current, torque, input power, output power, and efficiency. The PMSG output value will increase as the rotor rotational speed increases.